1987
DOI: 10.3354/dao003037
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and characteristics of the haemocyte parasite Bonamia sp. in the New Zealand dredge oyster Tiostrea lutaria

Abstract: Bonamiasis, first detected in the New Zealand dredge oyster Tjostrea lutaria (Hutton) during the southern autumn of 1986 was investigated through 2 surveys of oyster beds carried out over spring (Sep 1986) and summer (Jan 1987). In spring, a 'lighter' form of the parasite occurred most frequently, confined largely to the sub-epithelia1 tissue. In summer, a 'dense' form, nearly identical to the 'classic' European and American Bonamia ostreae, was the dominant type; it occurred in subsurface tissue around the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 3 publications
3
47
0
Order By: Relevance
“…Three species of Bonamia, B. ostreae (Pichot et al 1979, Carnegie et al 2000, Cochennec et al 2000, B. exitiosa (Dinamani et al 1987 and B. roughleyi (Farley et al 1988, Cochennec-Laureau et al 2003 are currently listed by the OIE. A PCR-restriction fragment length polymorphism (PCR-RFLP) assay has been proposed to distinguish between these 3 species ).…”
Section: Diagnosis Of Infection Withmentioning
confidence: 99%
“…Three species of Bonamia, B. ostreae (Pichot et al 1979, Carnegie et al 2000, Cochennec et al 2000, B. exitiosa (Dinamani et al 1987 and B. roughleyi (Farley et al 1988, Cochennec-Laureau et al 2003 are currently listed by the OIE. A PCR-restriction fragment length polymorphism (PCR-RFLP) assay has been proposed to distinguish between these 3 species ).…”
Section: Diagnosis Of Infection Withmentioning
confidence: 99%
“…The cup-like nuclear indentations with associated Golgi complexes and MVBs (Dinamani et al 1987, Hine 1991b, 1992, Hine & Wesney 1992, and the vacuolated stage (Hine 1991b) have not been reported from Bonamia ostreae. The reticulated structure (Hine & Wesney 1992), which may be connected to anastomosing endoplasmic reticulum (Hine & Wesney 1994a), and the Golgi associated with lipoid body genesis (Hine & Wesney 1994a) have not been described in B. ostreae.…”
Section: Comparison With Bonamia Ostreaementioning
confidence: 99%
“…It resembled Bonamia ostreae Pichot et al 1979 in Ostrea edulis in Europe and was therefore called Bonamia sp. (Dinamani et al 1987, Hine 1991a,b, 1992, 1996, Hine & Wesney 1992, 1994a,b, Hine & Jones 1994. Subsequent investigations have shown that the parasite was present in Foveaux Strait oysters in 1964, and a longstanding association between host and parasite is suggested by a consistent annual pattern of infection (Hine 1991a,b).…”
Section: Introductionmentioning
confidence: 99%
“…edulis in California in the past (Katkansky et al 1969) and more recently (Elston et al 1986, Friedman et al 1989. Bonamia sp., the subject of this study, is highly pathogenic in Tiostrea chilensis in Foveaux Strait on the south coast of the South Island of New Zealand (Dinamani et al 1987). and since 1986 has destroyed ca 80 % of the oyster stocks.…”
Section: Introductionmentioning
confidence: 99%